Advancements and hot research topics of artificial intelligence in mobile learning: a review of journal publications from 1995 to 2019. (25th October 2021) - Hwang, Gwo-Jen; Tu, Yun-Fang; Lin, Chi-Jen
Based on the Technology-based Learning model, the present study reviewed the Artificial Intelligence-supported Mobile Learning (AImL) studies by searching for journal articles published from 1995 to 2019 in the Scopus database. Various dimensions, such as countries/areas, authors, subject areas and subject categories, hot topics and adopted technologies, were considered in this review study. Regarding the hot topics of AImL studies, the main focuses were 'situated learning' in 1995-2007, 'mobile learning', 'intelligent tutoring systems' and 'ubiquitous learning' in 2008-2013, and 'mobile learning', 'artificial intelligence', 'machine learning' and 'intelligent tutoring systems' in 2014-2019. Moreover, in recent years, the number of applications regarding 'machine learning', 'artificial neural networks', 'cloud computing', 'data mining' and 'opinion mining' as well as other AI algorithms has been increasing. Accordingly, suggestions for future AImL studies are provided for the reference of researchers, teachers and educational policymakers.